PREVALENSI DAN FAKTOR RISIKO KOKSIDIOSIS PADA SAPI PERAH DI KABUPATEN BANDUNG (Prevalence and Risk Factor of Coccidiosis in Dairy Cattle in Bandung District) - Isrok Malikus Sufi; Umi Cahyaningsih; Etih Sudarnika (Universitas Syiah Kuala, 2016)
This study aimed to determine the prevalence and associated risk factors of coccidiosis. Samples were obtained from 400 dairy cattle (196 calves aged 6 months, 37 calves aged 6-12 months, and 167 calves aged 12 months). Feces samples were collected, examined and counted for prevalence and number of oocyst per gram faeces (OPG) by McMaster technique. A questionnaire was design to record information about animal health and husbandry, individually. Risk factors associated with the prevalence of Eimeria in cattle were analyzed by logistic regression model. The overall prevalence and the average of OPG of Eimeria in cattle was 179 (44.75%) and 286.75, while highest prevalence of Eimeria was observed in calves aged less than 6 months. Cattle aged more than 12 months showed significantly different relationship (P0.05) to the prevalence of Eimeria infection compare to calves aged less than 6 months and aged 6-12 months. The presence of an immature immune system in younger calves resulting in their higher susceptibility to coccidiosis. Among management and animal health practices, floor type and treatment of cattle influence the prevalence of Eimeria in cattle.